Une approche micro-macro pour le suivi de ssure avec enrichissement local - Guidault, Pierre-Alain; Allix, Olivier; Champaney, Laurent; Cornuault, Christian (European Journal of Computational Mechanics, 2006)
In this paper, a multiscale strategy for the analysis of crack propagation is presented. The purposes of this strategy are, rst, to separate the local effects from the global effects in order to keep a macromesh unchanged during the crack's propagation and, second, to enable one to use a proper ne-scale description only where it is required. Two aspects are discussed: the rst is the choice of the macroscale in order to include the macroeffect of a crack; the second is the use of a decomposition of the domain into substructures and interfaces in order to limit the use of the rened scale only around the crack. The integration of the X-FEM as a local enrichment method for the description of a crack is also presented.